Enhancing the role of regional development banks - Griffith-Jones, Stephany (UN New YorkUS, 2008)
Discusses priorities for new regional development banks (RDBs) or the expansion of existing ones. Examines the extent to which private financial markets or development banks fund developmentally necessary projects. Analyzes the best modalities through which financing should be made available, to maximize its developmental impacts. Discusses the structure of RDBs so they can reduce their cost of lending and increase poorer countries access. Provides initial calculations of resources necessary for significantly expanding developing country owned RDBs or creating new ones, on a scale that could contribute significantly to meet infrastructure finance and other developmnent needs.